A photocatalytic sp3 C–S, C–Se and C–B bond formation through C–C bond cleavage of cycloketone oxime esters. Issue 3 (20th December 2018) - Anand, Devireddy; He, Yuwei; Li, Linyong; Zhou, Lei
Abstract : The photocatalytic sulfuration, selenylation and borylation of cycloketone oxime esters through iminyl radical-triggered C–C bond cleavage were described. The reactions provide a unified approach to alkyl sulfur, selenium and boron compounds tethered to a synthetically useful nitrile group. Abstract : The photocatalytic thiolation, selenylation and borylation of cycloketone oxime esters through iminyl radical-triggered C–C bond cleavage were described. The reactions provide a unified approach to alkyl sulfur, selenium and boron compounds tethered to a synthetically useful nitrile group.